Prefrontal Cortex Activation During Verbal Fluency Task and Tower of London Task in Schizophrenia and Major Depressive Disorder - Xiang, Yilei; Li, Yuan; Shu, Chang; Liu, Zhongchun; Wang, Huiling; Wang, Gaohua (Frontiers in Psychiatry, 2021)
Background: Cognitive dysfunction is a common clinical feature of mental disorders. A number of near-infrared spectroscopy (NIRS) studies have shown reduced prefrontal activation during verbal fluency task (VFT) in schizophrenia (SZ) and major depressive disorder (MDD). But no studies have examined and compare the brain activation patterns during the Tower of London (TOL), which is another classic, high sensitivity executive function testing tool, in these two serious mental disorders. This study aimed to assess the characteristics of brain activation during there two different cognitive tasks in SZ and MDD patients. Methods: This study recruited 30 patients with SZ, 30 patients with MDD and 30 demographically matched healthy controls (HCs). The hemodynamic changes of the prefrontal cortex (PFC) were measured using 32-channel NIRS during performance of the TOL task and VFT task. Results: SZ patients showed poorer VFT performance than MDD patients and HCs, and the two patient groups showed poorer TOL performance than HCs. Compared to HCs, both of the patient groups exhibited a significant decreased activation in the extensive PFC. And particularly in certain channels in the dorsolateral PFC (DLPFC), SZ patients exhibited significantly decreased hemodynamic changes than the MDD patients. Conclusions: Patients with SZ and MDD have different levels of impairment in different cognitive domains and different patterns of brain activation during the two cognitive tasks. Further research is needed to determine the use of NIRS for clinical evaluation and diagnosis.